PERFORMANCE OF WIRELESS MEASUREMENT SYSTEM FOR SOIL PROPERTIES MONITORING - TSVETELINA GEORGIEVA (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2018)
A developed wireless microprocessor system based on ATmega328P microcontroller and Arduino sensors for measurement of soil properties is described in the paper. The accuracy of the proposed system is analized during the measurement of basic soil parameters – electrical conductivity and acidity. The system has been experimentally tested with soil samples from eight soil types and soil solution. The results for the soil parameters obtained with the wireless measurement system are compared with a reference measuring instrument. The presented wireless system for soil parameters monitoring shows good measurement accuracy sufficient for engineering research.